Enhancing Pre-Reading Skills of Slow Learners Through Integrated Montessori-Contextual Learning in Kindergarten - Utami, Sri; Ishartiwi, Ishartiwi (Journal of Innovation and Research in Primary Education, 2025)
Reading proficiency serves as a fundamental cornerstone for academic success, yet children with slow learning difficulties face significant challenges in developing pre-reading skills. This study investigated the effectiveness of integrating Montessori methodology with contextual learning approaches to enhance pre-reading capabilities among slow learners in kindergarten settings. A classroom action research design following the Kemmis and McTaggart model was employed over three weeks at State Kindergarten 1 Kongbeng. Three children aged 4-5 years with identified slow learning difficulties were purposively selected as participants. Data collection utilized structured observation checklists assessing nine pre-reading skill indicators on a four-point scale, implemented across two intervention cycles incorporating Montessori materials within contextual learning frameworks. Baseline assessments revealed significantly low pre-reading abilities across all participants (38-47%). Following the integrated intervention, substantial improvements were observed, with final achievement levels reaching 77-80%. All participants demonstrated notable progress in phonological awareness, letter recognition, sustained attention, and motor coordination skills. The overall improvement rates ranged from 33-39 percentage points, with particularly strong gains in environmental vocabulary and real-world connection capabilities. The findings provide compelling evidence for the effectiveness of integrated Montessori-contextual learning approaches in addressing the specific learning needs of slow learners. The multisensory nature of Montessori materials, combined with meaningful contextual connections, facilitated systematic skill development among children who typically struggle with abstract concept formation. These results support the potential of thoughtfully integrated pedagogical approaches to enhance educational inclusion and prevent future academic difficulties among vulnerable student populations.